ST2 and galectin-3 as novel biomarkers for the prediction of future cardiovascular disease risk in preeclampsia. (4th July 2022) - Atakul, Nil; Atamer, Yıldız; Selek, Şahabettin; Kılıç, Berna; Koktasoglu, Fatmanur
Abstract: The aim of this study was to investigate known cardiovascular disease (CVD) risk biomarkers galectin-3 (Gal-3) and human stromelysin-2 (ST2) levels in preeclampsia (PE) and normotensive pregnancies. A case-control study was conducted in a teaching and research hospital. We performed data analysis involving 45 pregnant women with PE and gestational week (GW) matched 35 normotensive pregnant women. The Gal-3 and ST2 levels were determined by using ELISA kit. Gal-3 values did not differ statistically between PE and control groups (535.1 ng/mL vs. 615.2 ng/mL) ( p > .05). ST2 value in the PE group was statistically significantly lower than the control group (33.3 pg/mL vs. PE, 54.5 pg/mL, p ˂ .05). >34 GW patients (late-onset PE) had statistically significantly lower Gal-3 values than the ≤34 GW patients (early-onset PE) (507.1 ng/mL vs. 769.6 ng/mL, p ˂ .05). Late-onset PE patients had significantly lower ST2 values than early-onset patients (26.4 pg/mL vs. 57.9 pg/mL, p ˂ .05). We assume that low Gal-3 values in early-onset PE show a higher risk of cardiac fibrosis although both early and late-onset PE patients had an increased CVD risk later in life. We found the superiority of ST2 levels to Gal-3 levels in PE pregnancies for CVD risk assessment. Impact Statement: What is already known about this subject? Preeclampsia (PE) in pregnancy is a known risk factor for future cardiovascular disease (CVD) and is also associated with increased mortality from ischaemic heart disease later in life. Studies that investigate patients with a higher risk for CVD in PE pregnancies are lacking. What do the results of this study add? We found different levels of two novel cardiac markers with PE and normotensive pregnancies, and also with early and late-onset PE pregnancies. What are the implications of these findings for clinical practice and/or further research? Different adaptive responses from patients during PE pregnancies via altered levels of cardiac markers could help clinicians to identify women with a higher risk of CVD.